2016
DOI: 10.1242/jcs.194480
|View full text |Cite
|
Sign up to set email alerts
|

Acute stimulation of glucose influx upon mitoenergetic dysfunction requires LKB1, AMPK, Sirt2 and mTOR–RAPTOR

Abstract: Mitochondria play a central role in cellular energy production, and their dysfunction can trigger a compensatory increase in glycolytic flux to sustain cellular ATP levels. Here, we studied the mechanism of this homeostatic phenomenon in C2C12 myoblasts. Acute (30 min) mitoenergetic dysfunction induced by the mitochondrial inhibitors piericidin A and antimycin A stimulated Glut1-mediated glucose uptake without altering Glut1 (also known as SLC2A1) mRNA or plasma membrane levels. The serine/threonine liver kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 103 publications
1
32
0
Order By: Relevance
“…Interestingly, the activation of Sirt1/AMPK axis by FR58P1a has a cyto-protective effect in TNBC cells, promoting cell survival and proliferation but inhibiting their ability to migrate. In non-tumoral MCF10A cells, the activation of Sirt1/AMPK axis by FR58P1a only induces an early metabolic remodeling toward glycolysis to maintain ATP levels as previously reported 65,66 , lacking pro-survival and anti-migratory effects. These results suggest that possible aberrant metabolic signaling accompanies Sirt1/AMPK activation in TNBC cells.…”
Section: Discussionsupporting
confidence: 64%
“…Interestingly, the activation of Sirt1/AMPK axis by FR58P1a has a cyto-protective effect in TNBC cells, promoting cell survival and proliferation but inhibiting their ability to migrate. In non-tumoral MCF10A cells, the activation of Sirt1/AMPK axis by FR58P1a only induces an early metabolic remodeling toward glycolysis to maintain ATP levels as previously reported 65,66 , lacking pro-survival and anti-migratory effects. These results suggest that possible aberrant metabolic signaling accompanies Sirt1/AMPK activation in TNBC cells.…”
Section: Discussionsupporting
confidence: 64%
“…47, 48 Similarly, chronic (5 weeks) CI inhibition induced a fully glycolytic phenotype in primary skin fibroblasts, associated with an extreme sensitivity to glucose withdrawal. 49 These findings led us to propose that BAY-induced CI inhibition might, in addition to increasing cellular ROS levels, induce a shortage of glucose contributing to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been widely demonstrated that organization of these complexes into supra-molecular structures, or supercomplexes, greatly enhances their stability and assembly [5], and also prevents excessive ROS generation [6]. Recent studies showed that the supercomplex association is highly dynamic, and finely tuned by different signaling pathways that are triggered by increased ROS/H 2 O 2 production [7,8], or by mito-energetic dysfunction [9]. This changing organization allows for metabolic compensatory responses that enable mitochondria to promptly sustain the needed levels of cellular ATP.…”
Section: Introductionmentioning
confidence: 99%